2022
DOI: 10.3390/life12070942
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Wharton Jelly Implants Do Not Trigger Collagen and Cartilaginous Tissue Production in Tracheal Injury in Rabbits

Abstract: Background: Tracheal lesions are pathologies derived from the most diverse insults that can result in a fatal outcome. Despite the number of techniques designed for the treatment, a limiting factor is the extent of the extraction. Therefore, strategies with biomaterials can restructure tissues and maintain the organ’s functionality, like decellularized Wharton’s jelly (WJ) as a scaffold. The aim is to analyze the capacity of tracheal tissue regeneration after the implantation of decellularized WJ in rabbits su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Foltz et al, 2022, in a similar study, which analyzed the properties of Wharton’s Jelly for 30 days in rabbits after a tracheal injury, suggested that despite its various characteristics as a biomaterial, this structure did not present histopathological benefits for the regeneration of tracheal tissue. In this study, cartilage formation was evaluated using the same Aggrecan marker, where there was no significant difference between the control and the Wharton’s Jelly groups over 30 days [ 17 ]. In another study, Simeoni et al (2021) evaluated a decellularized amniotic membrane as a framework for tracheal lesions using mesenchymal stem cells, finding cartilaginous tissue through the formation of immature collagen in the regions of the tracheal defects after 60 days [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foltz et al, 2022, in a similar study, which analyzed the properties of Wharton’s Jelly for 30 days in rabbits after a tracheal injury, suggested that despite its various characteristics as a biomaterial, this structure did not present histopathological benefits for the regeneration of tracheal tissue. In this study, cartilage formation was evaluated using the same Aggrecan marker, where there was no significant difference between the control and the Wharton’s Jelly groups over 30 days [ 17 ]. In another study, Simeoni et al (2021) evaluated a decellularized amniotic membrane as a framework for tracheal lesions using mesenchymal stem cells, finding cartilaginous tissue through the formation of immature collagen in the regions of the tracheal defects after 60 days [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another study focused on the amniotic membrane revealed that including an anti-inflammatory molecule supported tissue regeneration in the trachea, leading to the development of immature cartilage and collagen formation, thereby preventing the reduction of the tracheal lumen [ 16 ]. Furthermore, research on using Wharton’s jelly in tracheal regeneration found that implantation did not elicit adverse reactions such as rejection and extrusion [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…При создании КИК/ТИК in vitro важным условием для достижения высокой степени их сходства с естественной тканью является воспроизведение не только биохимических, но и биомеханических стимулов, обеспечивающих жизнедеятельность клеток в организме [ [18,19,24,25,[31][32][33]37], в 4 -только исследование in vivo (на животных) [34,41,43,44], и в 10 исследованиях были проведены оба типа доклинических испытаний [11,16,17,20,21,26,35,36,38,42]. Клинических исследований, отвечающих критериям включения, найдено не было.…”
unclassified